IMPLEMENTATION OF PRECAUTIONARY PRINCIPLE IN COAL MINING LICENSES IN CENTRAL BENGKULU REGENCY OF BENGKULU PROVINCE - Dede Frastien; Edra Satmaidi; Iskandar Iskandar (Universitas Bengkulu, 2021)
Coal mining license is a juridical instrument for businessmen to carry out coal mining activities. Coal mining license is also a preventive instrument to prevent coal mining activities from causing environmental damage and pollution. In the process of issuing and implementing coal mining licenses according to Law Number 32 of 2009 concerning Environmental Protection and Management, one must consider the precautionary principle, which is implemented by integrating environmental considerations, in making coal mining licenses decisions. However, coal mining activities carried out by 9 coal mining companies in the Watershed of Air Bengkulu, showed that there was environmental destruction and pollution seen along the Watershed of Air Bengkulu. This study aimed to determine the application of the precautionary principle to coal mining licenses and the legal consequences of coal mining license decisions that did not apply the precautionary principle. This research was conducted using juridical empirical/socio-legal research, and data analysis was carried out using a qualitative juridical approach. The results of this research showed that the government of Bengkulu Province has not applied the precautionary principle in the process and implementation of coal mining license in the Watershed of Air Bengkulu of Central Bengkulu Regency. The legal consequence of not applying the precautionary principle in the decision to issue 9 (nine) coal mining licenses which was an essential and material requirement in a decision to issue a permit was null and void (nietig van rechtwege) and could be canceled (vernietig baar), the government of Bengkulu Province has the authority to cancel the licenses decision because it is a State Administration official.